Reproductive effort reduces specific immune response and parasite resistance - Nordling, D. (1998)
If a trade-off exists between reproductive effort and immune function, life-history decisions may have important implications for parasite resistance. Here, we report effects of experimental manipulation of reproductive effort on subsequent specific immune function and parasite resistance in the collared flycatcher, Ficedula albicollis. Our results show that increased reproductive effort of females immunized with Newcastle disease virus (NDV) vaccine negatively affected the ability to respond with NDV-specific antibodies. We further show that increased reproductive effort increased the intensity of Haemoproteus infections and that such infections are associated with higher mortality. Our results thus provide support for the hypothesis that immune suppression caused by reproductive effort may be an important mechanism mediating the life-history cost of reproduction.